Síntese e caracterização de materiais à base de carbono para aplicação como sensor de gás - Sales, Bárbara Maria Campos (2019)
The development research with a synthesis material has possible to the preparation of samples with applicability in areas as adsorption, catalysis and sensors. Among them, it is important to develop tools for the broad field of application. Materials containing sp2 carbon such as graphene, graphite and carbon nanotubes, for example, have great potential for use in this field due to properties such as conductivity, chemical stability and low cost. Such materials that have carbon in their structure can be obtained from the decomposition of organic compounds or as by-products of catalytic tests, in which there is deposition of organic substances on the surface of the catalyst used in the reaction, the carbon base. The sensitivity of these materials for use in sensors can further be improved by functionalization or addition of another element (metal or metal oxide) in their composition. Therefore, materials containing metals/metal oxides immersed in a carbonaceous matrix were prepared for use as sensors, carbon being derived from the decomposition of the chitosan biopolymer, and the dehydrogenation reactions of ethylbenzene and dry reforming of the methane. Thus, in the first stage of the work, samples containing different chitosan/iron ratios were synthesized, as well as a sample containing only chitosan (Chts). In the second part of the thesis, the materials synthesized in the previous step were subjected to the dehydrogenation reaction of ethylbenzene and in the third step, a nickel containing catalyst was synthesized and tested in the dry reforming reaction of methane. After the synthesis procedures, the materials were characterized by TGA/DTA, TPO, FTIR, XRD, Mössbauer spectroscopy, TPR, N2 adsorption/desorption isotherms, Raman spectroscopy and SEM. The gas sensing tests for methanol with the samples resulting from the various synthesis processes were carried out at different temperatures and methanol concentrations, and the current variation was verified as a function of time. The tests indicated a good performance of the material, with a better result observed in the sample from the dry reforming reaction of methane, suggesting the use of the sample as a sensor for methanol. The adsorption test with the methylene blue dye in aqueous solution was also carried out with the higher proportion Chts/Fe sample and it was verified that the material could also be applied in the adsorption of dyes, its removal of the solution facilitated by sample magnetism.